Cerdik seperti Ular dan Tulus seperti Merpati: Berdasarkan Matius 10:16b - Arif Yupiter Gulo (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
In serving Him there are challenges that must be faced. Therefore, the Jesus give a strategy to face with according on Matthew 10:16 who is shrewd as serpents and harmless as doves. This article with qualitative research methods in the form of exegesis-hermeneutics. This exegetical method understands the meaning of the text of Matthew 10: 16b, which is indicated that in serving there is wisdom and sincerity that brings peace, because only peacemakers are became the children of God.